Further evidence that endometriosis is related to tubal and ovarian cancers: A study of 271, 444 inpatient women. (May 2021) - Capmas, Perrine; Suarthana, Eva; Tulandi, Togas
Highlights: The rate of tubal cancer is higher in women with pelvic endometriosis [adjusted odds ratio (OR) 2.80, 95 % confidence interval (CI) 1.84–4.27]. The rate of tubal cancer is also higher in women with adenomyosis (adjusted OR 4.88, 95 % CI 3.66–6.50). Similar associations were found between ovarian cancer and pelvic endometriosis and between ovarian cancer and adenomyosis. Abstract: Objective: To evaluate associations between endometriosis and tubal and ovarian cancers in a large population-based study. Methods: The Health Care Cost and Utilization Project – National Inpatient Sample databases from 2005 to 2014 were used in this study. Data on patients with a diagnosis of tubal or ovarian cancer and endometriosis (overall and subtypes including adenomyosis and pelvic endometriosis) using International Classification of Diseases, Ninth Edition, Clinical Modification codes were extracted. Logistic regression analysis was performed to evaluate associations between tubal and ovarian cancers and endometriosis. Adjustment was made for age, race, median income level, payment plan, hospital location and obesity. Results: Of 38, 800, 139 women aged >18 years who were hospitalized between 2005 and 2014, 271, 444 women with adenomyosis and/or pelvic endometriosis, 4289 women with tubal cancer and 133, 253 women with ovarian cancer were identified. The rate of tubal cancer was three-fold higher in women with endometriosis compared with women without endometriosis (0.03 % vs 0.01 %). The odds ratio (OR) adjusted for age, race, obesity, income and insurance type was 4.02 [95 % confidence interval (CI) 3.17–5.11; p < 0.01]. The rate of tubal cancer was higher in women with adenomyosis (0.04 % vs 0.01 %; adjusted OR 4.88, 95 % CI 3.66–6.50; p < 0.01) and women with pelvic endometriosis (0.02 % vs 0.01 %; adjusted OR 2.80, 95 % CI 1.84–4.27; p < 0.01) compared with women without these conditions. Similar associations were found between ovarian cancer and pelvic endometriosis and ovarian cancer and adenomyosis. Conclusion: Both pelvic endometriosis and adenomyosis are strongly associated with tubal and ovarian cancers.